2009
DOI: 10.1186/cc7965
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic epidural anesthesia reverses sepsis-induced hepatic hyperperfusion and reduces leukocyte adhesion in septic rats

Abstract: IntroductionLiver dysfunction is a common feature of severe sepsis and is associated with a poor outcome. Both liver perfusion and hepatic inflammatory response in sepsis might be affected by sympathetic nerve activity. However, the effects of thoracic epidural anesthesia (TEA), which is associated with regional sympathetic block, on septic liver injury are unknown. Therefore, we investigated hepatic microcirculation and inflammatory response during TEA in septic rats.MethodsForty-five male Sprague-Dawley-rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…It shows there is a possibility of regional anesthesia anti-inflammatory effects due to blockade of C fibers, 7 thereby reducing the production of cytokines 8 and block the activity of the sympathetic nerve fibers. [9][10] Therefore, postoperative pain caused primarily by tissue inflammation and activation of C-fibers by reducing the production of cytokines that may limit the inflammatory response after surgery and postoperative pain severity. 17,18,19 In research Yasukawa found that IL-6 induces the formation of an anti-inflammatory cytokine IL-10 11 thus with suppressed IL-6 in the RAM group cause lowered levels of increased in IL-10 compared with GAM group.…”
Section: Discussionmentioning
confidence: 99%
“…It shows there is a possibility of regional anesthesia anti-inflammatory effects due to blockade of C fibers, 7 thereby reducing the production of cytokines 8 and block the activity of the sympathetic nerve fibers. [9][10] Therefore, postoperative pain caused primarily by tissue inflammation and activation of C-fibers by reducing the production of cytokines that may limit the inflammatory response after surgery and postoperative pain severity. 17,18,19 In research Yasukawa found that IL-6 induces the formation of an anti-inflammatory cytokine IL-10 11 thus with suppressed IL-6 in the RAM group cause lowered levels of increased in IL-10 compared with GAM group.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy animals, TEA did not exert any effect on the evaluated microcirculation parameters. In a sepsis model induced by cecal ligation and perforation [18] , TEA was able to normalize the increase in blood flow to the liver and to decrease temporary leucocyte adhesion to the venular endothelium, but not the vasoconstriction of hepatic vasculature and temporary sinusoidal leukocyte adhesion, both induced by sepsis.…”
Section: Rabbits Hoganmentioning
confidence: 91%
“…Two studies by Freise et al [17,18] used intravital microscopy to assess hepatic microcirculation in different pathologic animal models. In acute pancreatitis in rats [17] , TEA prevented the vasoconstriction of sinusoids, but could not reduce the number of non perfused sinusoids.…”
Section: Rabbits Hoganmentioning
confidence: 99%
See 2 more Smart Citations